Social Interaction in Building Religious Tolerance in Sukabumi City Society - Handayani, Lusi; Kustana, Kustana (Jurnal Iman dan Spiritualitas, 2024)
This study aims to determine the understanding of society, social interaction in building religious tolerance and the role of religious institutions in maintaining religious tolerance in the community of Sukabumi. This form of study is qualitative and based on fieldwork using three methods including phenomenological method, sociological method, and historical method. The results of this study found that: first, the understanding of the people of Sukabumi about tolerance reflects an attitude of respect and acceptance of religious diversity, culture, and views. They actively interact with diverse backgrounds, respect human rights, and encourage interfaith and cultural participation in community activities. This understanding creates an inclusive, harmonious, and peaceful coexistence environment, which makes Sukabumi an inspiring example in building a tolerant society. Social interaction between citizens of different religions and effective social communication have established a social contract that respects and respects religious rights. Sukabumi's achievement as the 6th tolerant city in Indonesia shows the commitment of the government and society in promoting the values of tolerance. Positive factors, such as government policies, inclusive education programs, and public awareness, contributed to this achievement. Through the iceberg models approach, researchers can understand how social interaction fosters harmony and awareness of religious diversity. Understanding and respect for religious diversity is the hallmark of Sukabumi that must be strengthened in order to be an example of harmony for a diverse Indonesia.